2021
DOI: 10.1155/2021/5585291
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Poor Outcome of COVID-19 Patients on the Day of Admission with the COVID-19 Score

Abstract: Background. COVID-19 may result in multiorgan failure and death. Early detection of patients at risk may allow triage and more intense monitoring. The aim of this study was to develop a simple, objective admission score, based on laboratory tests, that identifies patients who are likely going to deteriorate. Methods. This is a retrospective cohort study of all COVID-19 patients admitted to a tertiary academic medical center in New York City during the COVID-19 crisis in spring 2020. The primary combined endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies showed that CKD is a risk factor for ICU admission and unfavorable outcome [ 7 , 8 , 22 ] partially due to persistent low-grade inflammation and dysregulated immune response [ 23 ]. In addition, CKD increases the risk for acute kidney injury and the need for renal-replacement therapy, a known complication of COVID-19 [ 22 , 24 ]. After performing a multivariate logistic regression analysis, the initial 2.652 OR value of e-GFR, as a marker of renal function and CKD stratification, subsided to aOR of 1.852, with borderline statistical significance ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that CKD is a risk factor for ICU admission and unfavorable outcome [ 7 , 8 , 22 ] partially due to persistent low-grade inflammation and dysregulated immune response [ 23 ]. In addition, CKD increases the risk for acute kidney injury and the need for renal-replacement therapy, a known complication of COVID-19 [ 22 , 24 ]. After performing a multivariate logistic regression analysis, the initial 2.652 OR value of e-GFR, as a marker of renal function and CKD stratification, subsided to aOR of 1.852, with borderline statistical significance ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Paradigmatic of this struggle is the amendments made by National COVID-19 Clinical Evidence Taskforce (NCCET) (Whang et al, 2021) that deleted the following statement from its revised guidelines "in patients with hypoxemia associated with COVID-19, do not routinely use NIV" (Whang et al, 2021). Since then, a number of studies dealt with the COVID-19 outcome prediction (Tseng et al, 2021), early vs. late intubation (Lee et al, 2021), and criteria for NIV and prediction of NIV failure Bellani et al, 2017;He et al, 2019), so that at present, the debate is still going and no definite recommendations are available, while patients are still largely ventilated with NIV, mainly in non-ICU departments and often by non-ICU trained physicians. An effort to provide clear and simple means to early discriminate patients that require intubation is thus needed, perhaps more due to ethical reasons than purely speculative ones.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, an increasing amount of studies are reporting successful treatment of SARS-CoV-2 pneumonia in non-intubated patients, ventilated with moderate to high level of positive airways pressure (PEEP/CPAP) (8-12 cmH 2 O) and cycles of awake proning (Bamford et al, 2020;Whang et al, 2021). Accurate selection of patients, appropriate PEEP/CPAP setting, and correct timing for switching to invasive mechanical ventilation in non-responders to the non-invasive approach are thus of paramount importance and still remain among the most debated topics in the intensive care unit (ICU) environment and more (Lee et al, 2021;Tseng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Topp et al (2021) demonstrated that patients who survived the infection had lower D-dimer, ferritin, lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) levels when they were intubated [2]. Alternatively, a multivariate model aimed at identifying the risk for poor outcomes applied on a sample cohort of 2,545 patients in New York City found that age, albumin, creatinine, C-reactive protein (CRP), and LDH were predictive variables [3]. Identifying at-risk patients is crucial for providing care and determining resource allocation based on patient risk stratification.…”
Section: Introductionmentioning
confidence: 99%